The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15294/maj.v9i3.36883
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Commitment in Improving Organizational Citizenship Behavior

Abstract: This study aims to examine the effect of work life balance, personality and organizational commitment on organizational citizenship behavior. The sample used in this study was 165 respondents. The sampling technique uses incidental sampling. Data analysis methods use descriptive analysis, regression analysis, and path analysis using IBM SPSS. The results showed that work life balance was not significantly positive effect, while personality and organizational commitment had a positive and significant effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…So, it can be given the meaning that the higher organizational commitment of employees will also increase the OCB of notary & PPAT employees in Bangli Regency. The results of this study are in line with the findings obtained by Hasani et al (2013), Prasetio et al (2015), Bazgir et al (2018), Bashir & Gani (2019), Siregar et al (2019), Fazriyah et al (2019), Wilkanandya & Sudarma (2020) who found that organizational commitment had a significant positive effect on OCB. While it is different from the findings obtained by Bone (2018), Grego-Planer (2019) who find that organizational commitment is not a significant positive effect on OCB.…”
Section: Discussionsupporting
confidence: 92%
“…So, it can be given the meaning that the higher organizational commitment of employees will also increase the OCB of notary & PPAT employees in Bangli Regency. The results of this study are in line with the findings obtained by Hasani et al (2013), Prasetio et al (2015), Bazgir et al (2018), Bashir & Gani (2019), Siregar et al (2019), Fazriyah et al (2019), Wilkanandya & Sudarma (2020) who found that organizational commitment had a significant positive effect on OCB. While it is different from the findings obtained by Bone (2018), Grego-Planer (2019) who find that organizational commitment is not a significant positive effect on OCB.…”
Section: Discussionsupporting
confidence: 92%
“…Variations in the level of employee commitment are also determined by numerous factors, both organizational and individual factors (Junita, 2017;Bodjrenou et al, 2019;Bodjrenou et al, 2019;Parimita et al, 2020). The previous research findings support this, stating that organizational commitment could significantly contribute to employee OCB (Ardi & Sudarma, 2015;Fazio, 2015;Devece et al, 2016;Pigome et al, 2019;Siregar et al, 2019;Wilkanandya & Sudarma., 2020) but also not significant (Novianti, 2021).…”
Section: Organizational Citizenship Behaviormentioning
confidence: 60%
“…The way individuals perceive organizational situations also contributes significantly to employee organizational commitment. The previous research results (Ardi & Sudarma, 2015;Fazio, 2015;Devece et al, 2016;Pigome et al, 2019;Siregar et al, 2019;Wilkanandya & Sudarma., 2020) have also proven that there was a substantial contribution of organizational commitment in making employees' OCB more dominant. Hence, this phenomenon justifies this research to place organizational commitment as a mediating variable between organizational antecedents, i.e., organizational support and individual antecedents, namely emotional intelligence, on employee OCB.…”
Section: Junita Hafas and Nasutionmentioning
confidence: 78%
“…H5 = Organizational commitment has a significant positive effect on organizational citizenship behavior Employees can easily carry out formal and informal behavior in the organization along with identifying the values associated with the organization. The stronger the identification of personal values associated with the organization, employees will be more likely to contribute to the organization as found by several studies (Fazriyah et al, 2019;Jehanzeb, 2020;Pahirathan, 2018;Pradhan et al, 2016;Soelton, Anees, et al, 2020;Soelton, Noermijati, et al, 2020;Utami et al, 2021;Wilkanandya & Sudarma, 2020). Therefore, this research hypothesis is that organizational commitment has a positive effect on organizational citizenship behavior.…”
Section: H3 = Work-life Balance Has a Significant Positive Effect On ...mentioning
confidence: 74%
“…Therefore, this research hypothesis is that organizational commitment has a positive effect on organizational citizenship behavior. H6 = Work-life balance has a significant positive effect on organizational citizenship behavior through organizational commitment as a mediating variable Employees who can manage work obligations and family responsibilities demonstrate organizational commitment which can encourage organizational citizenship behavior (Pradhan et al, 2016;Wilkanandya & Sudarma, 2020). Employees who are committed to the organization will be involved in both formal and informal behavior including job duties.…”
Section: H3 = Work-life Balance Has a Significant Positive Effect On ...mentioning
confidence: 99%